Enzyme-inspired supramolecular catalysis with metal-organic frameworks as scaffolds - Matseketsa, Pricilla (My University, 2025)
Metal-organic frameworks (MOFs) provide a versatile platform for constructing advanced catalysts due to their tunable structures and ability to incorporate diverse functionalities. To mimic the confined space of enzymes, uniform distribution of functional groups is crucial. A reliable strategy for obtaining uniformly multifunctionalized MOF materials is the independent post-synthetic modification (PSM) of MOFs containing multiple modifiable functional groups in well-defined locations. This thesis describes how we leverage the covalent post-synthesis modification (PSM) of MOFs, to introduce catalytic functionalities into a well-defined Zn-based pillared MOF, KSU-1, which consists of amine-bearing (BDC-NH₂) and hydroxyl-bearing (DPG) linkers. This modular system enables systematic tuning of catalytic properties. Reacting KSU-1 with various isocyanates revealed an unexpected selectivity, where hydroxyl groups reacted preferentially over amines, contrary to expectations observed from its previous reactions with other electrophiles. This selective functionalization enabled systematic modification of the hydroxyl groups of KSU-1 with hydrophobic isocyanates (isopropyl, tert-butyl, n-hexyl, and tetradecyl) while preserving the active amine group. We determined that systematically increasing the hydrophobicity of the pores results in a commensurate increase of catalyst efficiency for the amine-catalyzed Knoevenagel condensation. Additionally, to demonstrate the versatility of PSM, we introduced catalytic urea groups by selectively modifying the amine sites of KSU-1, while modification at the hydroxyls imparted secondary functionality to once again modulate the pore environment. We initially conducted the Henry reaction of benzaldehyde and nitroalkane in the presence of base. However, this reaction only proceeds with just the base, so the background reaction made it difficult to evaluate catalytic performance. We then shifted our focus towards the Friedel-Crafts alkylation of 3-methoxy dimethylamine with [beta]-nitrostyrene, using a urea-based MOF KSU-1MeU, produced from the functionalization of the amine groups of KSU-1. As expected, KSU-1 showed lower conversions of 14% compared to the 25% conversion observed for KSU-1MeU demonstrating the strength of urea’s two-point H-bond activation. We subsequently functionalized the hydroxyl groups in KSU-1MeU with isocyanate of varying electronics, sterics and, chirality to study the effect of this pore modulation on the catalytic activity and selectivity. Finally, to highlight the utility of post-synthetic modification in constructing catalysts with functional groups that are likely inaccessible via de novo synthesis (such as pendant carboxylic groups), while preserving independent and uniform functionalization, we developed a new PSM strategy. Previous methods for achieving independent functionalization have relied on the orthogonal reactivity of modifiable functionalities, or the significantly different reactivities of the modifying substrates. In a new strategy, we carefully selected reaction conditions and reagents in the functionalization of KSU-1 with cyclic anhydrides which allowed us to achieve stability of the initial post-synthetic product from the reaction of the amines (KSU-1Amide), allowing us to obtain homobifunctionalized and well-defined heterobifunctionalized KSU-1 derivatives for potential applications in catalysis.
Keywords: Metal-organic frameworks; Post synthetic modification; Unexpected reactivity; Amine based hydrophobic catalyst; Urea based bifunctional catalyst; Enantioselectivity